GEOCHEMISTRY, TECTONO-MAGMATIC DISCRIMINATION AND RADIOLARIAN AGES OF BASIC EXTRUSIVES WITHIN THE IZMIR-ANKARA SUTURE BELT (NW TURKEY): TIME CONSTRAINTS FOR THE NEOTETHYAN EVOLUTION - Cemal Göncüoglu, M.; Kenan Yalınız, M.; Kagan Tekin, U. (Ofioliti, 2006)
The Dağkuplu Mélange in the Central Sakarya Valley represents the northernmost outcrops of the Izmir-Ankara Suture Belt in northwest Anatolia. In addition to blocks and slivers of serpentinite, gabbro, blueschist, neritic and pelagic limestones, it includes blocks of basic volcanic rocks associated with radiolarian cherts, pelagic carbonates and mudstones.The preliminary geochemical data revealed the existence of a variety of basaltic rocks with magma types ranging in composition of MORB, IAT, OIB and CAB, in the mélange.The age of the radiolarian assemblage from a tectonic block of chert-mudstone alternation associated with OIB-type basalts within the mélange is assigned to early Berriasian - early Hauterivian, based on the co-occurrence of radiolarian taxa as Angulobracchia sp. cf. A. (?) portmanni, Godia nodocentrum, Pantanellium masirahense, Thanarla brouweri, Pseudoeucyrtis hanni, Svinitzium mizutanii, Mirifusus dianae s.l., Tethysetta boesii. Another block of chert-mudstone alternation associated with MORB-type basalts includes the following Cenomanian radiolarian fauna: Thanarla pulchra, Novixitus mclaughlini, Pseudodictyomitra pseudomacrocephala, Pseudodictyomitra tiara, Stichomitra communis.New findings from the Central Sakarya area combined with previous data of the authors reveal that the Izmir-Ankara Ocean started to open already in the Late Triassic. The formation of OIB-type intra-plate seamounts within the Izmir-Ankara Ocean began in late Bathonian and persisted until early Aptian. The the intra-oceanic subduction and the generation of supra-subduction-type volcanism started in early Santonian and the spreading-ridge of the Izmir-Ankara Ocean plate was not subducted until the Cenomanian.